Small states in the European Union coping with structural disadvantages - Panke, Diana (Ashgate Pub., 2010)
Based on more than 100 interviews with policy-makers and an analysis of a database on the negotiation activities of EU member states, this book explains how active participation is essential for the shaping success of small states and shows that small states are more influential with persuasion-based rather than bargaining-based strategies.